LOCAL RITUALS IN THE DIGITAL AGE: THE INTERSECTION OF RELIGIOUS TRADITIONS AND GLOBAL TECHNOLOGY - Abdul Wahab Syakhrani; Ismaul Fitroh; Moh. Imron Rosidi (Adisam Publisher, 2025)
This study discusses the transformation of local rituals in Indonesia in the face of the digital age, particularly at the intersection between religious traditions and the penetration of global technology. Through literature review and analysis of various sources, this study identifies patterns of adaptation in local rituals, ranging from virtual documentation and participation, the use of digital applications, to the emergence of new figures such as spiritual influencers. The findings reveal that digitalisation opens opportunities for the preservation and revitalisation of traditions, but also poses challenges such as the potential commodification of traditions, shifts in religious authority, and the risk of losing sacred meaning. Successful adaptation depends heavily on the community's ability to balance the use of technology with the protection of core traditional values. This study emphasises that technology can be a tool for cultural empowerment and preservation, provided it is used wisely and based on ethics that respect the essence of religious rituals